EFFECT OF SOAKING TIME AND CONCENTRATION OF GIBERELIN (GA3) ON THE GROWTH OF GARLIC (Allium sativum) VAR. SANGGA SEMBALUN - Syahmi Edi; Malem Teta Sinulingga (Universitas Negeri Medan, 2023)
This study aims to determine the germination of garlic (Allium sativum) var. Sangga sembalun to the treatment of soaking time and GA3 concentration. This research was conducted in the field of planting in Sukandebi Village, Naman Teran District, Karo Regency. This research was conducted from March to July 2022. The research design used was a factorial completely randomized design (CRD) with 2 factors and 4 replications. The first factor is the soaking time of GA3 which is 12 hours and 24 hours. The second factor was the concentration of GA3, namely 0 ppm, 3 ppm, 6 ppm, 9 ppm, and 12 ppm. The parameters observed consisted by time of seed germination, germination percentage, sprout height, and root length. The data obtained from this study were analyzed by analysis of variance (ANOVA) and to determine the best treatment, Duncan Multiple Range Test (DMRT) was conducted at the 5% significance level. The results of the study showed that the soaking time and GA3 concentration on garlic var. Sangga sembalun significantly affected all parameters of observation which are time of seed germination, germination percentage, sprout height, and root length. The results showed that the soaking time of garlic var. Sangga sembalun for 24 hours was able to speed up the time of emergence of sprouts, germination percentage, sprout height, and root length. The concentration of 15 ppm GA3 can accelerate the time to sprout and increase the percentage of germination, while the concentration of 9 ppm GA3 increases the sprout height and root length.